The Effect of Customer Trust on Repurchase Intention Through User-Generated Content as an Intervening Variable in The Automotive Industry Case Study @Bandarmotor_ - Dhea Sartika (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
Social media is used for brand awareness. Instagram ranks third as a media that is often used in Indonesia. Bandarmotor is a shop that provides spare parts and two-wheeled vehicle service services located in South Banyuwangi. If there is no increase in followers and decrease in turnover, research is carried out to find out whether it is true that customer trust will increase motivation to create user-generated content and the desire to repurchase Bandarmotor. The study population of Instagram followers of @bandarmotor_ account amounted to 1533 people. The study sample using the purposive sampling method was 73 people. Questionnaires using Google forms. The analysis method uses Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results showed that Customer trust had a significant positive effect on user-generated content. Customer trust has a significant positive effect on repurchase intention. User-generated has a significant positive effect on repurchase intention. User-generated content has a significant positive effect on customer trust and repurchase intention.